Third Party Logistics Relationship Success Factor in Vietnam - Ngo Ngoc Minh, (International Journal of Psychosocial Rehabilitation, 2020)
The paper demonstrates that several operational factors are critical needed to establish successful third party logistics relationship (TPLR) between automotive manufacturer (AM) and third party logistics provider (TPL). The five key operational factors examine are known as the use of technology, the price of logistics service, information sharing between AM and TPL, investment on asset and system, as well as logistics service performance. The discussion of the paper is conducted in three case studies in the automotive sector in Vietnam. The originality and novelty of the paper is on its unique context which is focus on the operational factor of TPLR in one specific industry namely automotive, in Vietnam, and the investigation is from a dyadic perspective. Key findings may give positive impact to the practitioners via the development of novel on TPLR (third party logistics relationship) success factor.